Problematika Hak Eksekutorial Jaminan Fidusia: Perspektif Kepentingan Debitur - Panjaitan, Wijaya Natalia; Lenggono, Roy Prabowo (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
A common problem in the enforcement of fiduciary guarantees is the seizure of collateral that violates consumer rights. Creditors often seize collateral without taking into account consumer rights protected by law. This can lead to disputes between the creditor and the debtor. The purpose of this research is to analyze the problems of fiduciary enforcement rights from the perspective of debtors' interests. The research method used is Normative Juridical Research with the type of library research. Debtors must check the credit agreement more carefully, in particular the clause